Power supply study for electrical devices cleaning and suspensions separation - Nazarenko, I. (Енергетика і автоматика, 2015)
The results of the study multiphase high voltage power supply devices for electric cleaning and separation slaboprovodidnyh suspensions. Compared waveforms of output signals of two frequencies with their calculated values. The possibility of using the proposed scheme the power source.